Typification of Glycine tomentella (Fabaceae: Phaseoleae) with comments on its internal groups - Gunner, Simon Thompson; Doyle, Jeff (Phytotaxa, 2014)
The legume Glycine tomentella had not been typified according to the rules of nomenclature for many years after it was described. While typification was attempted rather recently, the designated type material is currently missing. An appropriate replacement type is designated herein. Furthermore, the presence of intersterile, morphologically and molecularly diverged groups within the G. tomentella polyploid complex warrants an historical review and current perspective. The type material of this mainly Australian species is identified as belonging to a polyploid genome group that is found in Taiwan.